The Application of Teams Games Tournament (TGT) Type Cooperative Learning Model to Enhance Student’s Learning Activities - Izzanatun Ulfa Syahidah; Agus Efendi; A G. Tamrin (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2018)
The type of this research is Classroom Action Research was collaboratively conducted between computer system teacher with researcher in two cycles. Every cycles consist of four steps, which: planing, implementation, observation, and reflection. This Classroom Action Research aimed to improve Student Learning Activity on Academic Subjects of Computer System throught the implementation of Cooperative Learning Model Type Teams Games Tournament (TGT) with the help of Snakes and Ladders Game as the media. The subject of this research is the students of class X SMK N 6 Surakarta was numbered thirty two’s student. The data collection method in this research was used by participative observation, documentation, daily notes and interview. Analaysis of data used was descriptive data analysis of quantitative with percentage. This analysis was done by means of processing the score of Student Learning Activity, provides data, and conclusion.Based on the research results, it can be concluded that the implementation of Cooperative Learning Model Type Teams Games Tournament (TGT) on Academic Subjects of Computer System can improve Student Learning Activity in class X SMK N 6 Surakarta. The results of this show that there was an improvement in every indicators of Student Learning Activity from cycle I to cycle II. The increase number of score in average in the Student Learning Activity is amounted to 14,58% from the average score of Student Learning Activity cycle I amounting to 69,79% becomes 84,37% on cycle II. The percentage results in cycle II showed that score is already reached minimum criteria that was defined at the amount of 75%..